Persepsi Siswa tentang Metode Pembelajaran yang Digunakan Guru dan Hubungannya dengan Motivasi Belajar Ekonomi - Anne Cassandra; Z. Mawardi Effendi; Armida S (Universitas Negeri Padang, 2021)
Abstract : This research is a descriptive study which aims to determine how students perceptions of the learning methods used by the teacher, students motivation and the relationship between students perceptions of the learning methods used by teacher and the motivation to learn economic in class XI SMAN 3 Pariaman. This is done by distributing a questionnaire for students perceptions about the learning methods used by the teacher and a questionnaire on learning motivation to students. The statements in the questionnaire each consisted of 23 statements for students perceptions and 27 statements for learning motivation. The data analysis in this study used the distribution of scores, mean, tcr, and correlation analysis which could be used as a descriptive analysis. Based on the results of the study, it was found that students perceptions of the learning methods used by the teacher were categorized as good for indicators of conformity with student management in the class of 86,92%, students economic learning motivation in the high category for indicators of future hopes and aspirations of 81,77%, and there is a positive and significant relationship between perceptions of the learning method usedby teachers and students motivation to learn economics at SMAN 3 Pariaman stated strong enough by percentage of 38,44%.